Cerebral haemorrhagic risk in children with sickle‐cell disease. (30th August 2014) - Kossorotoff, Manoelle; Brousse, Valentine; Grevent, David; Naggara, Olivier; Brunelle, Francis; Blauwblomme, Thomas; Gaussem, Pascale; Desguerre, Isabelle; De Montalembert, Mariane
<x xml:space="preserve">Abstract</x> Aim To address risk of first or recurrent cerebral haemorrhage in children with sickle‐cell disease (SCD) who are being managed with modern stroke prevention strategies. Method A systematically followed SCD paediatric cohort was retrospectively studied over a 9‐year period. Haemorrhagic risk was defined as intracranial haemorrhage occurrence or intracranial aneurysm diagnosis during the study period. Ischaemic risk was defined as cerebrovascular ischaemic event occurrence or transcranial Doppler/magnetic resonance imaging hallmarks of ischaemic risk finding during the study period. Results Among the 251 patients in the cohort, 36 patients were included in the ischaemic group. Seven patients were included in the haemorrhagic group, of which five also met the criteria for the ischaemic group. Age at first haemorrhagic symptom/hallmark of risk was older (10.4 vs 6.2 years old, p=0.036). Nine intracranial saccular aneurysms were found, mostly on the posterior circulation. Two patients had endovascular embolization. Interpretation The ratio of ischaemic to haemorrhagic risk was not modified with modern management compared with historical series. Intracranial aneurysm in children with SCD had specific characteristics, close to intracranial aneurysms described in adults with SCD. Data favoured concurrent development of intracranial SCD‐associated anterior stenosis and posterior dilation, suggesting common pathophysiology and management strategies.